Implementation of a prospective pregnancy registry for antiretroviral based HIV prevention trials. Issue 1 (2nd January 2018) - Mhlanga, Felix G.; Noguchi, Lisa; Balkus, Jennifer E.; Kabwigu, Samuel; Scheckter, Rachel; Piper, Jeanna; Watts, Heather; O'Rourke, Colin; Torjesen, Kristine; Brown, Elizabeth R.; Hillier, Sharon L.; Beigi, Richard
Abstract : Background: Safety data on pregnancy and fetal outcomes among women in HIV prevention trials are urgently needed to inform use of effective antiretroviral agents for HIV prevention. We describe an effective, efficient, and novel method to prospectively collect perinatal safety data concurrent with on-going parent clinical trials. Methods: The Microbicide Trials Network (MTN)-016 study is a multinational prospective pregnancy exposure registry designed to capture pregnancy and neonatal outcomes. Studies currently contributing data to this registry included phase I and II safety trials with planned exposures to candidate HIV prevention agents, as well as phase IIB and III efficacy trials capturing data on pregnancy and infant outcomes following inadvertent fetal exposure during study participation. Results: To date, participants from two phase I studies and two effectiveness trials have participated in MTN-016, resulting in 420 pregnant women and 381 infants enrolled. Infant retention has been high, with 329 of 381 (86%) infants completing the 12-month follow-up visit. Conclusion: In a research setting context, it is feasible to establish and implement a prospective, multinational HIV chemoprophylaxis pregnancy registry that will generate pregnancy exposure data in a robust fashion.